AN ANALYTICAL STUDY ON THE EXPORT PERFORMANCE OF DAIRY INDUSTRY IN INDIA - Kumar, Shiv; Ansari, Kashif (International Journal of Research -GRANTHAALAYAH, 2016)
With the rise of factory farming, milk is now almost an unnatural operation. The modern dairy farm can have hundreds, even thousands of cows. Today’s average dairy cow produces six to seven times as much milk as she did a century ago. Currently, the United States is the largest producer of milk in the world, followed by India and China. India being one of the largest milk producer around the world, has to import a part of Milk products and its exports are negligible in the World Export Share. This paper tries to examine the issues regarding ‘Export Performance of Dairy Industry of India’: Trends, Challenges and suggestions for improving the trade situation. The existing Literature has been reviewed accordingly comprising Trade Exports, Imports and the factors which are affecting the Milk Production in country. The Objectives of the study is to find out the reasons for the low per unit production, Imports and negligible exports. In Nutshell, it can be said that there are many unexplored areas in which researchers can explore the findings which can be helpful in achieving trade balance of the Indian Economy.